Identification and characterization of a novel Plasmodium falciparum merozoite apical protein involved in erythrocyte binding and invasion. - Thilan Wickramarachchi; Yengkhom S Devi; Asif Mohmmed; Virander S Chauhan (PLoS ONE, 2008)
Proteins that coat Plasmodium falciparum merozoite surface and those secreted from its apical secretory organelles are considered promising candidates for the vaccine against malaria. In the present study, we have identified an asparagine rich parasite protein (PfAARP; Gene ID PFD1105w), that harbors a predicted signal sequence, a C-terminal transmembrane region and whose transcription and translation patterns are similar to some well characterized merozoite surface/apical proteins. PfAARP was localized to the apical end of the merozoites by GFP-targeting approach using an inducible, schizont-stage expression system, by immunofluorescence assays using anti-PfAARP antibodies. Immuno-electron microsopic studies showed that PfAARP is localized in the apical ends of the rhoptries in the merozoites. RBC binding assays with PfAARP expressed on COS cells surface showed that it binds to RBCs through its N-terminal region with a receptor on the RBC surface that is sensitive to trypsin and neuraminidase treatments. Sequencing of PfAARP from different P. falciparum strains as well as field isolates showed that the N-terminal region is highly conserved. Recombinant protein corresponding to the N-terminal region of PfAARP (PfAARP-N) was produced in its functional form in E. coli. PfAARP-N showed reactivity with immune sera from individuals residing in P. falciparum endemic area. The anti-PfAARP-N rabbit antibodies significantly inhibited parasite invasion in vitro. Our data on localization, functional assays and invasion inhibition, suggest a role of PfAARP in erythrocyte binding and invasion by the merozoite.